Team coverage, on-field care and injuries in Karate - Rosso, C.; Arnold, R.; Zenhäusern, R.; Willscheid, G. (sems-journal, 2021)
Abstract: In this article, the most important aspects of team coverage of Karate athletes with special focus on medical care of competitions are highlighted. A proposition of what a doctor`s case for martial arts competition should contain is given. According to the Swiss accident insurances, extremities are most frequently seen. During competitions, in our own series, over 70% of injuries are mild and do not need further treatment. However, the physician in charge of a tournament needs to be prepared also for severe injuries. The authors are currently conducting an ongoing, prospective study on injuries during Swiss national competitions since 2011. Zusammenfassung: In diesem Artikel werden die wichtigsten Aspekte der Teambetreuung im Karate aufgezeigt. Der Hauptfokus liegt jedoch auf der Wettkampfbetreuung. Ein Vorschlag für einen Arztkoffer, der mitgeführt werden sollte, wird aufgeführt. Laut den Schweizerischen Unfallversicherern sind Extremitätenverletzungen am häufigsten anzutreffen. Während Wettkämpfen konnten wir in eigenen Erhebungen ca. 70% leichte Verletzungen, die keine weitere Behandlung bedürfen, feststellen. Als betreuender Arzt muss man jedoch auch auf schwere Verletzungen vorbereitet sein. Die Autoren führen aktuell eine prospektive Studie über Verletzungen an den Schweizer Karate-Meisterschaften seit 2011 durch.